Descriptions of two new species of Hemileucinae (Lepidoptera: Saturniidae) from the region of Muzo in Colombiaevidence from morphology and DNA barcodes - Decaëns, Thibaud; Rougerie, Rodolphe (Zootaxa, 2008)
Two new species of Hemileucinae are described from the region of Muzo (Boyaca department) in the Eastern Cordillera of Colombia. Leucanella bonillensis, new species, is a small greyish species whose closest relatives are L. newmani (Lemaire) and L. acutissima (Walker). It can be distinguished from those two species by several subtle differences in wing pattern and coloration as well as a few characters of the male genitalia, which are overall very conserved within the genus. Cerodirphia zulemae, new species, belongs to the very uniform species-group of C. speciosa (Cramer), characterised by a pink ground colour and the presence of a “Y”-shaped discal mark on the forewing. Based on its male genitalia, the new species is related to C. brunnea (Draudt) and C. apunctata Dias & Lemaire. It may be distinguished from the former by its more vivid ground colour, but detailed examination of the male genitalia are necessary to differentiate it from C. apunctata. Colour pictures of the habitus of the new species and their relatives are provided, and their genital structures are figured as well, including both sexes for C. zulemae. We also provide additional support to these descriptions based on genetic data obtained in the context of a global DNA barcoding campaign recently initiated for saturniid moths. Both L. bonillensis and C. zulemae are unambiguously distinguished from closest relatives based on genetic distances (no intraspecific distances in either case; interspecific distance ranges 5.6–6.6% and 6.7–12.5%, respectively) and inference of phylogenetic hypotheses based on partial sequences of the COI mitochondrial gene. These results emphasize the potential of DNA barcoding to support taxonomic work in species-groups considered difficult to address through morphology.